Synoptic and Dynamical Characteristics of High-Impact Storms Affecting the Iberian Peninsula during the 2018–2021 Extended Winters - Ana C. R. Gonçalves; Raquel Nieto; Margarida L. R. Liberato (Atmosphere, 2023)
In the extended winters from December 2017 to April 2021, numerous high-impact storms affected the Iberian Peninsula (IP) with heavy precipitation and/or strong winds. Here, we provide a comprehensive assessment of these events, synoptic conditions, large-scale dynamics associated with storms, and a climatological analysis to improve public awareness and natural disaster prevention. Variability analysis presents that their maximum intensity ranges from 955 hPa to 985 hPa, a two-to-four-day lifetime, and the highest frequency (eight events) occurred in January. At the instant of maximum intensity, anomalies presented low MSLP values (−21.6 hPa), high values of water vapor (327.6 kg m−1s−1) and wind speed at 250 hPa (29.6 m s−1), high values of θe at 850 hPa (19.1 °C), SST (−1 °C), and QE (−150 W m−2), near Iberia. The values obtained during the storm impact days exceeded the 98th percentile values in a high percentage of days for daily accumulated precipitation (34%), instantaneous wind gusts (46%), wind speed at 10 m (47%), and concurrent events of wind/instantaneous wind gusts and precipitation (26% and 29%, respectively). These results allow us to characterize their meteorological impacts on the IP, namely those caused by heavy precipitation and wind.